1986
DOI: 10.1111/j.1471-6402.1986.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Productive Activity: The Relationships Among Self-Concept, Gender, Sex Role Stereotypes, and Work-Emergent Traits

Abstract: A theoretical framework is presented that focuses on the division of labor by gender to account for both sex role stereotypes and the correspondence between these stereotypes and the self‐concepts of women and men. According to this framework, the self‐images of adults are largely constituted by attributes generated by their productive activity. These attributes, referred to as work‐emergent traits, are consequences of working within particular social and physical conditions of production because they help ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 33 publications
0
16
0
2
Order By: Relevance
“…For example, although elementary students' occupational stereotypes decrease with age, their actual occupational choices become more stereotyped (O'Keefe & Hyde, 1983). Researchers have concluded that the belief that certain occupations are appropriate only for a single sex is greatly influenced by observation of division of labor by sex (Eagly & Steffen, 1986;Krefting, Berger, & Wallace, 1978;Yount, 1986). It is more important to see nontraditional career choices being made by both women and men than it is to be told by counselors that women have the ability to become crane operators and boys have the ability to become art teachers.…”
Section: Occupational Segregation As An Antecedent To Occupational Chmentioning
confidence: 99%
“…For example, although elementary students' occupational stereotypes decrease with age, their actual occupational choices become more stereotyped (O'Keefe & Hyde, 1983). Researchers have concluded that the belief that certain occupations are appropriate only for a single sex is greatly influenced by observation of division of labor by sex (Eagly & Steffen, 1986;Krefting, Berger, & Wallace, 1978;Yount, 1986). It is more important to see nontraditional career choices being made by both women and men than it is to be told by counselors that women have the ability to become crane operators and boys have the ability to become art teachers.…”
Section: Occupational Segregation As An Antecedent To Occupational Chmentioning
confidence: 99%
“…While working in sex‐typed occupations, stereotypical masculine or feminine traits emerge and form the GRSC of the respective jobholders. Following Yount's theoretical argument, a masculine GRSC will emerge from masculine activities at work. Contrary, drawing on Fraley and Roberts' () work on stability and change of personal characteristics, interactional processes (people proactively seek situations that fit their personalities well) may also take place here.…”
Section: Discussionmentioning
confidence: 99%
“…Young women with more traditional gender beliefs tend to have more traditional work and family plans (Novack and Novack 1996;Stringer and Duncan 1985;Weeks et al 1984;Yount 1986;Zuckerman 1981) and lower leadership aspirations (Boatwright et al 2003). In addition, resource dilution theory suggests that young women with more siblings may receive less parental time, energy, and financial resources (Blake 1989;Downey 2001;Powell and Steelman 1989) which may lower their occupational aspirations.…”
Section: Contextual Factors Associated With Career-relevant Decisionsmentioning
confidence: 95%